Body image perceptions and marital adjustment levels of married persons in public secondary schools in Anambra State, Nigeria - Ifeanyi Mathew Azuji; Anthonia Nneka Obumse; Uju Christiana Nwanna; Esther Chinyere Ejichukwu; Anulika Valentina Etele; Obianuju Blessing Mokwelu; Helen Efeyadu Uzoekwe (Academia Mental Health & Well-Being, 2025)
How people think about their bodies has become a big issue in modern society, affecting many parts of their health and relationships with others. However, not much research has been conducted on the link between how people feel about their bodies and how well they are adjusting to marriage. This is especially true when it comes to how these feelings affect the marriages of teachers, counsellors, and other non-teaching staff who work in public secondary schools in Anambra State, Nigeria. This study examines the relationship between body image perceptions and marital adjustment levels among married persons in public secondary schools in Anambra State. Employing a correlational research design, the study addresses three research questions to assess the extent and direction of the relationship between these variables. A sample of 1280 married persons was selected from a population of 4887 through multi-stage sampling. Data were gathered using the two research instruments adapted for the study. Data were analyzed using SPSS, with percentages summarizing the data and the Pearson Product Moment Correlation Coefficient assessing relationships. The results indicated that 57.4% of participants had a healthy body image perception, while 42.6% had a low perception. Additionally, 93.2% reported good marital adjustment, while 6.8% were maladjusted. A very low positive correlation was found between body image perceptions and marital adjustment. This study recommends that school management invests in professional development for counsellors, focusing on contemporary issues related to body image, self-esteem, and marital counselling to enhance support for staff members.